Documents as Displaced Voice: Writing among Amazonian Urarina. (21st October 2016) - Walker, Harry
Abstract: Despite apparently low levels of literacy, Urarina people of Peruvian Amazonia engage enthusiastically with written documents. Focusing on their performative qualities, or what documents "do, " this article explores their use and appropriation in relation to local ideologies of language and power. While serving an important role in linking people to the Peruvian state and its highly bureaucratic political culture, it is argued that documents are especially valued, and deemed capable of extending personal influence and persuasive power, because of three overlapping capacities or tendencies. They displace or delegate voice and detach it from agency, thus constructing an image of a distant or even transcendental authority; they transduce across semiotic modalities, suggesting the mediation of relations with nonphenomenal worlds; and they fix discourse, hinting at the possibility of permanence in a fluid social environment.[Amazonia, bureaucracy, documents, literacy, orality, writing]